Is non-ablative 1550-nm fractional photothermolysis an effective modality to treat melasma?: Results from a prospective controlled single-blinded trial in 51 patients - Karsai, Syrus; Raulin, Christian (Journal of the European Academy of Dermatology and Venereology, 2012)
Background Melasma is a common benign pigmentary disease and can pose a substantial therapeutic challenge. Although the use of non-ablative fractional photothermolysis (NFP) has gained much popularity, there are still very few evidence-based data supporting NFP in the treatment of melasma. Objective To assess the efficacy and safety of NFP for the treatment of melasma in a controlled observer-blinded parallel-group study. Patients and methods Fifty-one patients [90.2% women, 9.8% men; mean age 40.3 ± 6.1 (control group) and 41.7 ± 11.4 (treatment group)] received a broad-spectrum sunscreen either alone (n = 25; 49.0%) or in combination with a 1550-nm NFP treatment (n = 26; 51.0%) [energy: 15 mJ/microthermal zone (MTZ); total density: 1048 MTZs/cm2; density per pass: 131 MTZs/cm2; number of passes: 8; total coverage: 20%]. Four sessions of NFP treatment were performed at 3-week intervals on each subject in the treatment group. Patients were evaluated at baseline and 12 weeks after final treatment. The primary efficacy variables were the Melasma Area and Severity Index (MASI) and the physician’s global assessment (PGA); secondary efficacy variables were the patients’ subjective assessment of improvement and patient satisfaction. Safety was evaluated through the reporting of adverse events. Results The percentage of subjective improvement was virtually identical in both groups: one-third of the patients reported a ‘marked improvement’ and another half reported ‘some improvement’. Twenty-three patients in each group declared that they were ‘satisfied’ with the treatment result. The MASI corroborated the patients’ subjective estimate, both in terms of the degree of improvement and the lack of a group difference. In both groups, the MASI score and the PGA were reduced significantly after therapy, and the reduction was also clinically relevant. No serious side-effects were reported in either group. Conclusion Our findings do not support the hypothesis of NFP providing a substantial benefit in treating melasma when compared with the lone application of a broad-spectrum sunscreen.